2013
DOI: 10.1126/science.1242575
|View full text |Cite
|
Sign up to set email alerts
|

Human Influences on Nitrogen Removal in Lakes

Abstract: Human activities have increased the availability of reactive nitrogen in many ecosystems, leading to negative impacts on human health, biodiversity, and water quality. Freshwater ecosystems, including lakes, streams, and wetlands, are a large global sink for reactive nitrogen, but factors that determine the efficacy of freshwater nitrogen removal rates are poorly known. Using a global lake data set, we show that the availability of phosphorus, a limiting nutrient, affects both annual nitrogen removal rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
189
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 307 publications
(200 citation statements)
references
References 70 publications
9
189
2
Order By: Relevance
“…Whereas, N:P ratio decreased in all N lakes and two W lakes probably indicating that the reduced N input from the lake catchments resulted in a decrease in N:P ratio in the absence strong decline in P concentrations. However, reduced phosphorus concentrations in lakes have been proposed to lead to a decrease in N removal efficiency [66]. An analysis of long-term time series for 12 deep lakes showed a marked increase in N concentrations following a sharp decrease in P concentrations, despite stable or decreasing N inputs [66].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, N:P ratio decreased in all N lakes and two W lakes probably indicating that the reduced N input from the lake catchments resulted in a decrease in N:P ratio in the absence strong decline in P concentrations. However, reduced phosphorus concentrations in lakes have been proposed to lead to a decrease in N removal efficiency [66]. An analysis of long-term time series for 12 deep lakes showed a marked increase in N concentrations following a sharp decrease in P concentrations, despite stable or decreasing N inputs [66].…”
Section: Discussionmentioning
confidence: 99%
“…The increased availability of reactive nitrogen in many ecosystems as a result of human activities has had negative impacts on human health, biodiversity, and air and water quality (Vitousek et al, 1997;Galloway et al, 2008;Finlay et al, 2013). In freshwater ecosystems, high levels of human-generated ammonia (NH 4 + ), nitrite (NO 2 − ), and nitrate (NO 3 − ) may produce harmful effects on aquatic organisms (Constable et al, 2003;Camargo et al, 2005;Camargo and Álonso, 2006;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the decrease of sinking organic matter under low phosphorus levels, processes such as denitrifi cation and long-term storage (burial) in aquatic ecosystems are weakened because of a low energy supply. This could result in more N export downstream, which could exacerbate nitrogen pollution problems in sensitive waters (Bernhardt, 2013;Finlay et al, 2013). As a semi-enclosed lake, the northern part of Lake Taihu has suffered serious nitrogen pollution related to P-only control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments and lake restoration practices have shown that P-only reduction strategies succeed in preventing eutrophication in many lakes (Schindler, 1977;Schindler and Vallentyne, 2008;, except for several large and medium-sized shallow lakes with the infl uence of internal P release (Havens et al, 2001). However, P-only reduction strategies lead to excess N benefi ting the non-N 2 -fi xing cyanobacteria, such as Planktolyngbya , Oscillatoria , and toxic Microcystis (Conley et al, 2009), and result in a higher N-load reaching other areas (Finlay et al, 2013). Co-limition of N and P has been reconsidered and supported by some experiments (Elser et al, 2007;Paerl et al, 2011;Moss et al, 2013), which proved that P-only reduction strategies were not a good choice for eutrophication prevention and algal bloom control on a large ecological scale (Bernhardt, 2013).…”
Section: Introductionmentioning
confidence: 99%